Neonatal mortality trends at tertiary care hospital, Kuppam - Dr. Haricharan K R; Dr. Gowtham R.; Dr. Rajendra Naidu; Dr. Harsha P J.; Dr. Chandrashekar M.A. (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Neonatal mortality rate is one of the indicators which depict the health care status of that country. Hospital based mortality and morbidity pattern helps in improving the quality of health care delivery in the hospital. Objectives: (1) To determine the neonatal mortality trend over 36 months and various causes of neonatal mortality. (2) To determine the risk factors for early and late neonatal deaths. Study Design: Retrospective study. Study Population: Neonates admitted to Neonatal Intensive Care Unit (NICU). Study Duration: From January 2015 to December 2017. Methodology: Systematically and retrospectively charts were reviewed using data recorded in Neonatal Intensive Care Unit (NICU) at PESIMSR, Kuppam, Andhra Pradesh. Results: A total of 2089 neonates were admitted to Neonatal Intensive Care Unit (NICU) between January 2015 to December 2017. Average Neonatal Mortality Rate (NMR) between January2015 to December 2017 was 7.5%. Early neonatal deaths were 35(49.3%) and Late Neonatal death was 36(50.7%). Common causes of death were neonatal sepsis, perinatal asphyxia and prematurity and its complications. Conclusions: Implementing appropriate strategies to improve antenatal, perinatal and neonatal care helps in preventing perinatal asphyxia, neonatal sepsis and prematurity and its complications, which further helps in reduction of neonatal mortality, in-turn decreases the infant mortality and under 5 mortality rate.